Whole-cell biocatalysis: Advancements toward the biosynthesis of fuels - Madavi, Tanushree Baldeo; Chauhan, Sushma; Keshri, Anushri; Alavilli, Hemasundar; Choi, Kwon Young; Pamidimarri, Sudheer D.V.N. (Biofuels, Bioproducts and Biorefining, 2022)
The availability of robust microbial systems has facilitated the implementation of greener technology replacing existing less sustainable chemical technologies. Whole-cell biocatalysis has empowered the biological production of chemicals and biofuels, replacing labor-intensive traditional chemical catalysis. Whole-cell biocatalysis offers new avenues to use sustainable raw/waste biomass as a substrate for biotransformation into industrially important compounds. Using a native or non-native microbial cell system as a chassis for developing a suitable cell catalyst requires multiple-level adjustments owing to the target product. Enzymes, the critical entity of biocatalysis, are an important factor influencing biocatalysis efficiency; whole cells provide optimal conditions to the enzymes or enzyme cascades for maximum productivity. Advancements in system biology and metabolic engineering techniques have led to the rational design of whole-cell catalysts for the suitable production of green fuels. Traditional enzyme catalysts are limited by issues such as enzyme stability and repeatability, laborious downstream processing and enzyme production technicalities, but whole-cell biocatalysis could bypass those bottlenecks. Thus, the application of whole cells in the catalysis and production of fuels has progressed greatly in the past couple of decades. This review focuses on detailing the concept of whole-cell biocatalysis and its advances in the production of biofuels such as alcohols and fatty acid-based, terpenoid-derived and carbon-free fuels. The technical advancements in various hosts such as Escherichia coli, Saccharomyces cerevisiae, Corynebacterium glutamicum and Synechococcus elongatus to establish whole-cell biocatalysis are summarized. In addition, system engineering toward the optimum production of various biofuels is added to the discussion. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd.
Keywords: Advanced biofuels; Biocatalysis; Biological production; Chemical catalysis; Chemical technologies; Green technology; Labour-intensive; Microbial system; Whole cell; Whole-cell biocatalysis; advanced biofuels; alcohols; biodiesel; biofuels; biomass; whole-cell biocatalysis